PENGARUH ESG TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Seluruh Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2021) - Gabriela, Natasha; Prabowo, Tri Jatmiko Wahyu (Diponegoro Journal of Accounting, 2024)
In this research, the authors examined the direct influence of ESG performance on company financial performance as well as through earnings management as a mediating variable. The author perform this research based on the consideration to examine factors outside financial information that could influence the company's financial performance. The data used in this research is secondary data involving 75 companies listed on the Indonesia Stock Exchange in 2021. The method used to collect data in this research is through documentation and literature studies. Regression analysis was performed with IBM SPSS 26 software to examine the direct and indirect effect of ESG on financial performance. The results of this study indicate that ESG has a positive and significant effect on the company's financial performance. Meanwhile, earnings management is unable to mediate the relationship between ESG and financial performance. These findings indicate that companies with high ESG scores tend to have high financial performance as well.